THE ARCHITECTURE OF VIRTUAL SPACE MUSEUMS - Sfintes, Anda-Ioana (European Scientific Journal, ESJ, 2013)
Using the internet is more than a trend if we are to acknowledge the fact that it does not only shape its users, but it also reflects the changes that take place at a social level through everything that the user itself gives back to the network, through users interactions in virtual space, through consumption and demands virtually stated etc. As we pass from searching to sharing, playing or shopping on-line, we realize that between these theoretically distinct actions the boundaries blur. We identify this movement towards unclearness all around us and more and more profound lately (for example, in guerilla theatre or multifunctional buildings). In this context, the virtual museum, eMuseum or online museum are exhibition forms that further expand, blur, interweave defining characteristics of the museum with other kinds of activities not rarely considered opposed to it. Many museums have already added up to their physical exhibitions virtual tours or on-line exhibitions (some even created especially for the internet). The experiential differences between on-line/on-site museums are many and important, answering to different needs. However, all the more so as we admit that, by visiting an exhibition, we do not only experience the display layout, but also the space itself, we can further ask ourselves what happens with the curatorial discourse and architecture in virtual space. The aim of this article is to find a response to this question by analyzing the place, role and impact of architecture in the case of virtual space museums.